Well‐dispersed poly(ether‐ether‐ketone)/multi‐walled carbon nanotube nanocomposites prepared via a simple solution mixing approach. Issue 8 (12th April 2021) - Jiang, Zhiyuan; Chen, Qihui; Zhu, Zewen; Tsai, Chia‐Ying; Zhao, Mingzhen; Sue, Hung‐Jue; Chang, Andy; Bremner, Tim; DiSano, Lorenzo P
Abstract: Incorporation of reinforcing nanoparticles, like multi‐walled carbon nanotubes (MWCNTs), in a polymer matrix is an effective way to enhance mechanical properties and expand structural applications of engineering polymers such as poly(ether‐ether‐ketone) (PEEK). Good dispersion of MWCNTs is critical for achieving optimal properties. In this work, a simple solution mixing approach was utilized to prepare PEEK nanocomposites reinforced with MWCNTs. By direct mixing of PEEK/dichloroacetic acid solution and MWCNT/ N ‐methyl‐2‐pyrrolidone solution, PEEK nanocomposites with individually dispersed MWCNTs were prepared. A PEEK wrapping of MWCNT mechanism is proposed to explain why this simple solution mixing approach resulted in such a good dispersion. Thermal stability of PEEK is not affected but crystallization is impeded due to the confinement effect of well‐dispersed MWCNTs. Young's modulus is increased by ca 20% while coefficient of thermal expansion above the glass transition temperature is decreased by ca 30% with only 1.5 wt% MWCNT loading in PEEK, which is critical for a variety of high‐temperature applications. © 2021 Society of Industrial Chemistry. Abstract : PEEK/MWCNT nanocomposites prepared via a solution mixing approach show good dispersion, high mechanical reinforcement and good thermal and dimensional stability.